COMPARISON BETWEEN TWO TYPES OF MATRIX SYSTEMS FOR CONTACT TIGHTNESS IN CLASS-II COMPOSITE RESTORATIONS - Muhammad Asif,; Imran Khattak ,; Qureshi, Asim; Muhammad Zain,; Naveed Aslam,; Muhammad Izaz Khan, (Journal of Ayub Medical College Abbottabad, 2023)
Background: The reconstruction of proximal defects with tight contacts has always been a challenge for dental clinicians, especially with composite material. Recent literature shows that the most frequently used matrix systems for restoration of proximal cavities are circumferential or sectional matrix band systems. The objective of this study was to compare the contact tightness that is achieved with these two matrix band systems when using composite material. Methods: A total of 30 patients, i.e., 60 cavities were selected in this quasi-experimental study. Since patients with two cavities in the posterior teeth were selected. Both the cavities where restored with circumferential system, i.e., Tofflemire and sectional matrix band system, i.e., Palodent plus on the same appointment. Hence both systems were used in every patient and then contact tightness assessed based on an evaluation criterion, i.e., FÃ©dÃ©ration Dentaire Internationale clinical criteria for evaluation of contact in direct and indirect restorations. To make a comparison between the two systems chi square test was used and p<0.05. Results: The mean age of the patients in the study was 31 years (SD, 7.59 years) with range from 18 to 45 years. Most of the contact tightness in Palodent matrix system was score 1 (n=33, 55%) and score 2 (n=17, 28.3%) while in Tofflemire was score 4 (n=28, 46.7%) and score 5 (n=19, 31.7%). Statistical analysis showed significance (p=.037) between Palodent matrix system contact tightness and Tofflemire. Conclusion: The sectional matrix band system was statistically superior to the circumferential matrix band system in achieving a tighter contact for class II composite restorations